Bringing their worlds back: using photographs to spur conversations on everyday place. Issue 1 (2nd January 2016) - Bendiner-Viani, Gabrielle
Abstract : This article poses a methodological argument for the use of expressive photographs in fostering more mindful discussions of the experience of everyday places. The article builds on the author's 'guided tours' methodology of walk/make/talk, which involves asking inhabitants to take the researcher on tours of their everyday places, the researcher making creative visual representations of those places and then, bringing those images back to residents to talk about how the photographs are similar, or in contrast, to lived experience. The article uses examples from research in Brooklyn, NY, and Oakland, CA, to specifically explore the 'making' and 'talking' part of the process, and to argue for the critical distance gained when a participant has the opportunity to see their most commonplace and often unremarked worlds brought back to them through another pair of eyes. The paper considers distinctions with other photo-elicitation methods and discusses how this model of bringing people's worlds back to them often allowed the jolt of a new perspective to suspend the taken-for-grantedness of the world, creating a time and opportunity to consider the everyday in more depth. It further discusses how the method enabled people to clarify three aspects of everydayness that are hard to pin down: the feel of place, emotional responses, and seeing past time. The paper challenges conceptions of photographs as 'data', champions expressive work in research, and proposes that photographs made by a range of authors can enable new ways of seeing, challenging and discussing the everyday urban environment.